Cephalopod-inspired versatile design based on plasmonic VO2 nanoparticle for energy-efficient mechano-thermochromic windows - Ke, Yujie (2020)
Privacy and energy-saving are key functionalities for next-generation smart windows, while to achieve them independently on a window is challenging. Inspired by the cephalopod skin, we have developed a versatile thermo- and mechano-chromic design to overcome such challenge and reveal the mechanism via both experiments and simulations. The design is facile with good scalability, consisted of well-dispersed vanadium dioxide (VO2) nanoparticles (NPs) with temperature-dependent localized surface plasmon resonance (LSPR) in transparent elastomers with dynamic micro wrinkles. While maintaining a fixed solar energy modulation of (ΔTsol), the design can dynamically control visible transmittance (Tvib) from 60% to 17%, adding a new dimension to VO2-based smart windows. We prove that the optical modulation relies on the microtexture-induced broadband diffraction and the plasmon-enhanced near-infrared absorbance of VO2 NPs. We further present a series of modified designs towards additional functionalities. This work opens an avenue for independent dual-mode windows and it may inspire development from fundamental material, optic, and mechanical science to energy-related applications.